Robust Mechanism Design and Social Preferences - Felix Bierbrauer; Axel Ockenfels; Andreas Pollak; Désirée Rückert (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study a classic mechanism design problem: How to organize trade between two privately informed parties. We characterize an optimal mechanism under selfish preferences and present experimental evidence that, under such a mechanism, a non-negligible fraction of individuals deviates from the intended behavior. We show that this can be explained by models of social preferences and introduce the notion of a social-preference-robust mechanism. We characterize an optimal mechanism in this class and present experimental evidence that it successfully controls behavior. We finally show that this mechanism is more profitable only if deviations from selfish behavior are sufficiently frequent.
Keywords: C92; D03; D82; 330; robust mechanism design; social preferences; bilateral trade